Šalutiniai kirčiai vakarų aukštaičių kauniškių tarmėje - Kazlauskienė, Asta (Kalbotyra, 2001)
In the south-western Aukštaitian dialect the word-final vowels in the endings which could basically possess the main stress (sg. genet. -ės, -os, sg. nomin. -ė, -a, sg. locat. -e, pl. genet. -ų, pres. t. 1 person -i) are longer than those of never stressed word-final vowels (pl. nomin. . -ės, -os, pres. t. 3 person -a, -ia, past. t. 3 person -ė, subj. m. -ų, pres. t. 3 person -i). The statistical analysis shows that these are reliable vowel length differences. As the vowel length is one of the most distinct features of the stress occurrence, the statement that longer word-final vowels have the secondary morpheme stress is possible.Investigation of the length of the same quality vowels in the same word obviously shows that the length of short vowels may also depend on the secondary stress. The short vowels in the second post-stressed syllable are on the average 1.2 times longer than the vowels in the post-stressed stem; the short vowels in the second pre-stressed syllable are 1.1 times longer than the vowels in the pre-stressed vowels. These are statistically reliable differences in the length of vowels. The differences of the vowel quantities are more vivid, when the secondary rhythmic stress coincides with the secondary morpheme stress.The long vowels of the third post-stressed syllable as well as the post-stressed end of word vowels are undoubtedly shorter than the second post-stressed vowel (compare: the ratio of the quantity of vowels in the investigated examples: pamã.to. : pérsimato. : pǽrmato. = 1 : 1 : 1.2; pérsišluoste̲. : pašlúoste̤. : pǽršluoste̲. = 1 1.1 1.2). This proves completely that the length of vowels in word-final position depends on the secondary rhythmic stress, which occurs in the second post-stressed syllable.